Metabolomic and Lipidomic Approaches to Evaluate the Effects of Eucommia ulmoides Leaves on Milk Quality and Biochemical Properties - Teng, Zhanwei; Wang, Linfeng; Du, Hongyan; Yang, Gaiqing; Fu, Tong; Lian, Hongxia; Sun, Yu; Liu, Shenhe; Zhang, Liyang; Gao, Tengyun (Frontiers in Veterinary Science, 2021)
Eucommia ulmoides leaves (EUL) contain a variety of natural bioactive compounds including chlorogenic acid, geniposide acid, and aucubin. These bioactive chemicals improve immune function and regulate lipid metabolism. The aim of this study was to investigate the effects of EUL on the biochemical properties of milk. Twenty Holstein dairy cows were randomly allocated to two groups fed a control (CTR, diet without EUL, n=10) or EUL (diet containing 3% EUL, dry matter, n=10) diet for 55 d. At the end of the experimental period (d55), milk samples were collected and analyzed to determine their composition. Though levels of milk fat, protein, lactose, and total milk solids were similar between the groups, small molecules, metabolites, lipids, and cytokines differed. Compared with the CTR group, the EUL group had an improved cluster of differentiation (CD)4/CD8 ratio (P<0.05) and lower interleukin (IL)-8 and IL-6 content (P<0.05). Metabolomics analysis identified 14 metabolites including 7Z,10Z,13Z,16Z,19Z-docosapentaenoic acid (FC=3.129), adrenic acid (FC=2.830), and eicosapentaenoic acid (FC=1.685) as having significantly increased in the EUL group (P<0.05) while 11 metabolites, including indole-2-carboxylic acid (FC=0.636), cholic acid (FC=0.430), and creatine (FC=0.784) had significantly decreased (P<0.05). Based on a constructed metabolome map, linoleic acid metabolism had the highest impact value for EUL. A total of 21 lipid classes and 1094 lipid species were detected in the milk by lipidomic analysis, among which 40 differed significantly between the CTR and EUL groups. The present findings showed that the EUL altered milk composition. Correlation analysis showed that 7Z,10Z,13Z,16Z,19Z-docosapentaenoic acid, adrenic acid, and eicosapentaenoic acid levels were negatively correlated with those of the inflammatory factors IL-6 and IL-8 (P<0.05), indicating that EUL improved milk quality by reducing inflammatory factors and increasing the CD4/CD8 ratio. Overall, our data demonstrate that EUL had positive effects on milk antioxidant parameters, immune indices, and micro-composition metabolism, thereby improving milk quality.